Climate change justice - Posner, Eric A., 1965-; Weisbach, David A. (Princeton University Press, 2010)
Climate change and justice are so closely associated that many people take it for granted that a global climate treaty should--indeed, must--directly address both issues together. But, in fact, this would be a serious mistake, one that, by dooming effective international limits on greenhouse gases, would actually make the world's poor and developing nations far worse off. This is the provocative and original argument of Climate Change Justice. Eric Posner and David Weisbach strongly favor both a climate change agreement and efforts to improve economic justice. But they make a powerful case tha.